The role of “green” licences in defining environmental controls in Norwegian salmon aquaculture - Nikitina, Ekaterina (UiT The Arctic University of Norway, 2015)
The study examines the problem of externalities in the Norwegian aquaculture sector. The two main environmental challenges of Norwegian salmon aquaculture at the moment are the sea lice spread and farmed fish escape. Without dealing with these challenges, no increase in production was possible. At the same time the growth in the output is needed to satisfy the increasing demand for salmon products on the global market. The allocation of “green” aquaculture licences in 2013 was an attempt to find a compromise. New licences were sold to producers under the condition that they will use new technologies for effective prevention of sea lice infestation and escape incidents. In this thesis the role of “green” licences in designing environmental controls is discussed. These regulations are seen as an important experiment that provided new economic information that can be studied and used for new environmental policy. The theory of externalities and pollution control is applied to the problem of sea lice, which is studied as biological pollution. The damage and abatement cost of the sea lice pollution is studied in order to discuss possibilities of using direct and market-based control instruments. By a simple assessment of the costs of different abatement methods applied on “green” farms, it was demonstrated that the technological development plays an important role in forming the economy-wide marginal abatement cost function. Key words: aquaculture, Atlantic salmon, green licences, pollution, externalities, damage of pollution, abatement cost, command-and control instruments, market-based instruments.